Diversity and interaction of common bacterial blight disease-causing bacteria (Xanthomonas spp.) with Phaseolus vulgaris L. - Tugume, Joab K.; Tusiime, Geoffrey; Sekamate, Allan Male; Buruchara, Robin Arani; Mukankusi, Clare Mugisha (Elsevier, 2019)
Common bacterial blight (CBB) is associated with common bean (Phaseolus vulgaris L.), an important grain legume for human consumption worldwide. The disease, caused by Xanthomonas spp. is spread mainly through seed. This paper focuses on the diversity of X. axonopodis pv. phaseoli and X. fuscans subsp. fuscans and interactions between related bacteria and the bean host. Review has suggested that the diversity and taxonomic studies of these pathogens are not exhaustive, especially in areas where detailed molecular analysis has not been conducted and previous characterizations were based on phenotypic features and PCR-based techniques. Also, no study has confirmed differential pathogenicity on bean genotypes based on compatible versus incompatible reactions. However, isolates react differently to wild and domesticated bean sources of resistance in common bean genetic backgrounds. A systematic approach will be required to investigate global changes in gene expression among different sources of resistance in a common bean background. The bacterial isolates that cause CBB should be functionally characterized using genotypes containing major quantitative trait loci (QTL) for CBB resistance. These studies will increase understanding of resistance and how it is manipulated by pathogens.